Towards a new research model in legal translation: future perspectives in the era of asymmetry - Vidal Claramonte, Maria Carmen África (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
The global society we live in leads to clashes and asymmetry between cultures. In this context, translation and legal studies play a fundamental but also very sensitive role. The old concepts of the Enlightenment, Reason, universalism, objectivity or the universal no longer serve any purpose either in the field of translation or in that of law. This paper proposes a research model based on post-structuralist concepts such as those of “differend”, “representation” or “aporia”. This model can help us conceive new ways of translating legal texts in the future that are more in line with the asymmetrical problems of our contemporary society.